ANALISIS DETERMINAN MINAT INDIVIDU DOSEN DAN MAHASISWA TERHADAP BANK SYARIAH - Rahman, Taufikur (IAIN Salatiga, 2014)
This study empirically examined the effect of attitude, subjective norms andPerceived Behavioural Control to intention and intention to actual behaviorof syaria banking transactions. This study used survey method to collecteddata. The respondents of this study are lecturers that worked at STAINSalatiga and students that studied at study program of syaria banking STAINSalatiga. Of the 100 questionnaires sent, questionnaires were completed andreturned are 86 questionnaires. Dependence methods has used to statistictest in this study. This study has utilized simple regression and multipleregression analysis to analyze the effect of attitude, subjective norm andPerceived Behavioural Control to intention and intention to actual behaviorof syaria banking transactions. Data will be process by stepwise method andenter method of Statistic Program for Social Sciences (SPSS). The result ofthis study suggest that empirically attitude, subjective norm dan perceivedbehavioural control partially and simultaneously has a positif and significantimpact to intention of syaria banking transactions. Intention variable alsohas a positif and significant impact to actual behavior of syaria bankingtransactions.